Why Women Wear High Heels: Evolution, Lumbar Curvature, and Attractiveness - Lewis, David M. G.; Russell, Eric M.; Al-Shawaf, Laith; Ta, Vivian; Senveli, Zeynep; Ickes, William; Buss, David M. (Frontiers in Psychology, 2017)
Despite the widespread use of high-heeled footwear in both developing and modernized societies, we lack an understanding of this behavioral phenomenon at both proximate and distal levels of explanation. The current manuscript advances and tests a novel, evolutionarily anchored hypothesis for why women wear high heels, and provides convergent support for this hypothesis across multiple methods. Using a recently discovered evolved mate preference, we hypothesized that high heels influence women’s attractiveness via effects on their lumbar curvature. Independent studies that employed distinct methods, eliminated multiple confounds, and ruled out alternative explanations showed that when women wear high heels, their lumbar curvature increased and they were perceived as more attractive. Closer analysis revealed an even more precise pattern aligning with human evolved psychology: high-heeled footwear increased women’s attractiveness only when wearing heels altered their lumbar curvature to be closer to an evolutionarily optimal angle. These findings illustrate how human evolved psychology can contribute to and intersect with aspects of cultural evolution, highlighting that the two are not independent or autonomous processes but rather are deeply intertwined.